HIGH AWARENESS, LOW SCORES: UNVEILING THE CONTRADICTION BETWEEN METACOGNITIVE REFLECTION AND WRITTEN MATHEMATICS TEST PERFORMANCE - Nur Riski Hasanah; Turmudi Turmudi; Dadang Juandi (EDU-MAT: Jurnal Pendidikan Matematika, 2026)
This study aims to describe students’ levels of metacognitive reflection and their written test performance in mathematics learning, as well as to analyze the relationship between the two. The study employed a mixed-method approach with a descriptive–correlational design involving 24 seventh-grade junior high school students selected through purposive sampling. Data were collected using a 10-item metacognitive reflection questionnaire (4-point Likert scale) and a written mathematics test consisting of two open-ended questions. The questionnaire demonstrated acceptable reliability (Cronbach’s Alpha = 0.768). Descriptive analysis indicated that most students were categorized at moderate to high levels of metacognitive reflection. However, Pearson correlation analysis revealed no significant relationship between metacognitive reflection and written test performance (r = −0.152, p = 0.479). These findings suggest that students reported metacognitive reflection does not necessarily correspond to their performance on written mathematical tasks. The results highlight the need for further investigation using multiple data sources to better understand the relationship between metacognitive reflection and mathematical performance. Keywords: Metacognitive Reflection, Written Test, Mathematics Learning, Academic Performance, Awareness